Promotion of colorectal neoplasia in experimental murine ulcerative colitis. Issue 1 (July 1996) - Okayasu, I; Ohkusa, T; Kajiura, K; Kanno, J; Sakamoto, S
Abstract : BACKGROUND: The mechanisms underlying the frequent development of colorectal carcinomas in patients with ulcerative colitis are still unknown. AIMS: To evaluate whether mucosal necrosis and regeneration act as enhancing or promoting factors in colorectal tumorigenesis, development of multiple colorectal tumours was studied in a murine model of ulcerative colitis with azoxymethane pretreatment. METHODS: Periods of chronic ulcerative colitis in mice were induced by three repeated administrations of 3% dextran sulphate sodium subsequent to a single azoxymethane pretreatment, to give conditions similar to the clinically observed active and remission phases. RESULTS: In the chronic colitis group with carcinogen exposure, multiple mucosal tumours (10.5/mouse) developed in the colorectum. This occurred primarily on the left side of the large intestine or transverse colon, the sites of the most severe colitic injury. The observed lesions were high grade dysplasias and invasive adenocarcinomas. Increased cell proliferation was evidenced by high uptake of bromodeoxyuridine, and increased activities of thymidylate synthetase and thymidine kinase. No tumours were induced in the control groups with azoxymethane pretreatment or chronic colitis alone. CONCLUSIONS: Repeated mucosal erosion with necrosis and regeneration is critical for the development of colorectal tumours in this experimental colitis system.